The Antimalarial Activity of the Water Extract of Simpur (Dillenia Indica L) Leaves against Plasmodium Berghei in Mice - Hafrizal Riza; Andhi Fahrurroji; Supriyanto Supriyanto; Arif Wicaksono (Majalah Obat Tradisional, 2019)
Malaria, caused by the climate of the subtropical area and the forest with many rivers and immovable water, is a contagious disease that still becomes a health problem in West Kalimantan. Simpur is a plant that is used by the locals to cure malaria. Therefore, this research aims to study the antimalarial activity in vivo and the 50% inhibitory concentration (IC50) of the water extract of Simpur leaves (Dillenia indica L) against Plasmodium berghei. This research used Peter Test method that used 7 test groups based on the test solution namely positive control group that was given dihydroartemisinin+piperaquine (DHP), negative control that was given aquabidestilata and the test group that was given the water extract of  Simpur leaves with various doses of 20, 40, 60, 80 and 100 mg/Kg BB of mice, which each group was given the test solution for 3 days. The result shows that the water extract of Simpur leaves could lower the parasitemia count with IC50 19,22 mg/kg BB.